Risk factors and adverse outcomes of extubation failure in preterm infants ≤32 weeks with neonatal respiratory distress syndrome - Zhu, Chen; Wang, Zhengli; Liu, Kaizhen; Li, Jiacheng; Tang, Wenyan; Shi, Yuan; Zhu, Qingxiong (Frontiers in Pediatrics, 2025)
ObjectiveInvasive mechanical ventilation (IMV) is a critical intervention for neonatal respiratory distress syndrome (NRDS). However, the high incidence of extubation failure and its adverse impact on preterm outcomes make the optimal timing of extubation a key clinical concern. This study aimed to identify risk factors for initial IMV extubation failure and analyze associated adverse outcomes in neonates ≤32 weeks’ gestation with NRDS, to provide evidence-based guidance for clinical decision-making.MethodA retrospective cohort study was conducted in the neonatal ICU (NICU) of Jiangxi Maternal and Child Health Hospital from January 2021 to May 2024, including neonates ≤32 weeks with NRDS who are required to receive IMV within 72 h postnatal. Patients were stratified into a success group (n = 228) and a failure (n = 62) group based on whether reintubation was required within 72 h post-extubation. Multivariable logistic regression and nomogram modeling were employed to analyze independent risk factors.ResultsA total of 290 cases were included, comprising 228 in the successful extubation group and 62 in the failed extubation group, yielding an extubation failure rate of 21.4%. Univariate analysis revealed that the extubation failure group had significantly lower gestational age, birth weight, weight at extubation, and initial serum albumin levels (p < 0.05) but higher Day 1 fluid intake, fraction of inspired oxygen (FiO₂) before extubation, incidence of patent ductus arteriosus (PDA) >1.5 mm, and Grade 3 or higher intraventricular hemorrhage (IVH) (p < 0.05). Additionally, maternal Ureaplasma urealyticum (UU) infection and placental abruption were more prevalent in the extubation failure group (p < 0.05). Multivariate logistic regression identified maternal UU infection, placental abruption, lower weight at extubation, higher FiO₂, Grade 3 or higher IVH, and PDA >1.5 mm as independent risk factors for extubation failure (p < 0.05). A nomogram model incorporating these six factors demonstrated a sensitivity of 91% and a specificity of 52% for predicting extubation failure, with an area under the curve (AUC) of 0.77. The extubation failure group had higher incidences of atelectasis and bronchopulmonary dysplasia (BPD) and required longer IMV duration during hospitalization (p < 0.05).ConclusionLower body weight at extubation, higher FiO₂, patent ductus arteriosus (PDA >1.5 mm), Grade 3 or higher intracranial hemorrhage, maternal Ureaplasma urealyticum infection, and placental abruption during pregnancy are independent risk factors for the failure of the first IMV extubation in neonates ≤32 weeks gestational age with NRDS. Extubation failure significantly increases the risk of atelectasis and BPD and prolongs the duration of invasive ventilatory support.